Assessment of Feed Supplementation to Dairy Goat: Results of Research and Technology Dissemination Trials - Anwar, Muhammad Zubair; Ali, Akhter; Khan, M. Azeem; Shah, Nisar Ali; Saeed, Ikram (Asian Journal of Agriculture and Rural Development, 2012)
Over the years, role and strength of dairy goat is increasing in Barani Tract of Punjab. The bread and butter needs of poor and small household are largely depends on livestock specifically on the dairy goats. The 80 percent livestock management activities are mostly depends upon women; therefore under the experimentation of feed supplementation mainly women's were included as research partners. The women perceptions regarding the effectiveness of feed supplement were collected by using a well structured questionnaire. A total of 62 women's were included in the sample size. Results indicated that 95.08% women's had shown their complete satisfaction from the feed supplements given to dairy goats. A large majority of the respondents (98.31) were in view that the given feed supplements had increased their milk productivity. Overall, 82.69 % sample women had pointed out that their knowledge about goat management has increased with this experimentation. Both empirical and experimental data shows a significant increase in milk yield i.e 520 ml and 562 ml respectively. The marginal rate of returns from milk was about 246.38 % that also revealed economic significance of the feed supplementation intervention to the dairy goats. The sustainability of feed supplementation has serious problem, about 67.27 percent respondents were in view that feed supplementation to dairy goat will not sustain due to resources poorness, availability and relatively importance of goat in household economy.